Disrupting HIV‐1 capsid formation causes cGAS sensing of viral DNA. (27th August 2020) - Sumner, Rebecca P; Harrison, Lauren; Touizer, Emma; Peacock, Thomas P; Spencer, Matthew; Zuliani‐Alvarez, Lorena; Towers, Greg J
Abstract: Detection of viral DNA by cyclic GMP‐AMP synthase (cGAS) is a first line of defence leading to the production of type I interferon (IFN). As HIV‐1 replication is not a strong inducer of IFN, we hypothesised that an intact capsid physically cloaks viral DNA from cGAS. To test this, we generated defective viral particles by treatment with HIV‐1 protease inhibitors or by genetic manipulation of gag . These viruses had defective Gag cleavage, reduced infectivity and diminished capacity to saturate TRIM5α. Importantly, unlike wild‐type HIV‐1, infection with cleavage defective HIV‐1 triggered an IFN response in THP‐1 cells that was dependent on viral DNA and cGAS. An IFN response was also observed in primary human macrophages infected with cleavage defective viruses. Infection in the presence of the capsid destabilising small molecule PF‐74 also induced a cGAS‐dependent IFN response. These data demonstrate a protective role for capsid and suggest that antiviral activity of capsid‐ and protease‐targeting antivirals may benefit from enhanced innate and adaptive immunity in vivo . Synopsis: Viruses must avoid or block activation of an interferon response in order to replicate. HIV‐1 uses its capsid to physically protect viral reverse transcripts from detection by the DNA sensor cGAS, thus disruption of capsid integrity/stability enhances innate immune sensing that may be harnessed therapeutically. Treatment of HIV‐1 with protease inhibitors or mutation of protease cleavage sites in gag leads to defective Gag cleavage, reduced particle infectivity and diminished capacity to saturate restriction factor TRIM5α. Gag cleavage defective viruses, unlike wild‐type HIV‐1, activate a potent interferon response in THP‐1 cells and primary macrophages. Innate immune activation is dependent on viral reverse transcription and the cellular DNA sensor cGAS. Treatment of HIV‐1 with capsid destabiliser PF‐74 also leads to a potent cGAS‐dependent interferon response. The HIV‐1 capsid physically masks viral DNA from innate immune detection. Abstract : HIV‐1 uses its capsid to physically protect viral reverse transcripts from detection by the DNA sensor cGAS, thus disruption of capsid integrity/stability enhances innate immune sensing that may be harnessed therapeutically.